Isostigma resupinatum (Coreopsideae, Asteraceae), a new species from Central Plateau, Goiás State, Brazil - Bueno, Vinicius R.; Morais, Isa L.; Nakajima, Jimi N. (Phytotaxa, 2019)
The new species Isostigma resupinatum is described and illustrated. It is morphologically similar to Isostigma sparsifolium, from which it differs mainly in its entire, subulate, and resupinate leaves. Distribution maps and phenological data are included.